THE EFFECT OF SCIENTIFIC APPROACH COMBINED WITH ERRQ STRATEGY VIEWED FROM TEXT TYPES ON THE EIGHTH GRADE STUDENTS’ READING COMPETENCY AT SMP SANTO YOSEPH DENPASAR - ., LUH WIDIANI; ., PROF. DR. DEWA KOMANG TANTRA, M.Sc.; ., DR. NI MADE RATMININGSIH, M.A. (Jurnal Pendidikan dan Pembelajaran Bahasa Indonesia, 2016)
Penelitian ini fokus pada 1) pengaruh pendekatan ilmiah kombinasi dengan strategi ERRQ dalam kemampuan membaca siswa kelas delapan ; 2) perbedaan pengaruh pendekatan ilmiah kombinasi dengan strategi ERRQ dilihat dari jenis teks dalam kemampuan membaca siswa kelas delapan. Metode penelitian ini meliputi. Populasi yang digunakan adalah siswa dari SMP Santo Yoseph Denpasar. Sampel penelitian pada kelas 8 SMP Santo Yoseph Denpasar dengan menggunakan Random Sampling. Data yang dianalisis menggunakan One-Way-ANOVA. Hasil menunjukan bahwa : 1) ada pengaruh signifikan pada pendekatan ilmiah kombinasi dengan strategi ERRQ dalam kemampuan membaca siswa dengan total nilai mean (X: 77.27) (?:0.01) ;2) perbedaan pengaruh pada pendekatan ilmiah kombinasi dengan strategi ERRQ dilihat dari jenis teks dalam kemampuan membaca siswa namanya naratif teks (X 76.47), recoun teks (X:78.78), diskriptif teks (X: 76.83). Kata Kunci : Kemampuan Membaca, Pendekatan Ilmiah, Strategi ERRQ, dan Jenis Teks The problems were focused on the following, they are: 1) the main effect of scientific approach combined with ERRQ strategy on the eighth graders? reading competency, 2) the differences of the effect of scientific approach combined with ERRQ strategy viewed from text types on the eighth graders students? reading competency. The research methods were the following. The population included students at SMP Santo Yoseph Denpasar. The samples were recruited from the eighth grade of SMP Santo Yoseph Denpasar. They were recruited using a Random Sampling. Data were collected by means a Posttest. The obtained data were analyzed by means of One-Way ANOVA. The results show the following: 1) there is a significant effect of scientific approach combined with ERRQ strategy on the students? reading competency which total mean score (X: 77.27) (?: 0.01) ; 2) The differences of the effect of scientific approach combined with ERRQ strategy viewed from text types on the students? reading competency could be arranged consecutively as follows: narrative text (X 76.47), recount text (X:78.78), descriptive text (X: 76.83). keyword : Reading Competency, Scientific Approach, ERRQ Strategy, Text Types